Double reputation and multi-angle weight-based cooperative spectrum sensing method against SSDF attacks - Zhiguo SUN; Zhao WANG; Zengmao CHEN; Rongchen SUN (Tongxin xuebao)
In order to improve the ability of cooperative spectrum sensing to withstand spectrum sensing data falsification (SSDF) attacks, a double reputation and multi-angle weight-based cooperative spectrum sensing (DRMW-CSS) method was proposed.Firstly, a scoring reputation was obtained by multiple iterations of historical local decision results, and an accuracy reputation was calculated on this basis.Secondly, secondary users (SU) were screened by double reputation and multiple reputation thresholds.Then, the impact of SSDF attacks on the screening method was judged and divided into three situations.Finally, the final global decision was made using the corresponding multi-angle weight data fusion decision method according to different situations.Simulation results show that the proposed method has good sensing accuracy when facing SSDF attacks with different attack strategies and probabilities, and has better anti-attack capability compared to traditional methods.